2012
DOI: 10.1007/s00264-012-1542-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes after anterior cruciate ligament reconstruction with quadrupled hamstring autografts and additional bone plug augmentation at five year follow-up

Abstract: Purpose Hybrid fixation has been proposed to improve outcomes of anterior cruciate ligament (ACL) reconstructions. This study evaluated midterm outcomes after transfemoral graft fixation using either a conventional or a modified technique using additional bone plug augmentation (BPA) of the femoral tunnel aperture. Methods Seventy-one consecutive patients undergoing ACL reconstruction using a quadrupled hamstring autograft with transfemoral graft fixation and tibial interference screw fixation were included. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Substantial interest has arisen in the ability of anterior cruciate ligament reconstruction (ACLR) to restore normal functional knee mechanics; as well, it is of interest whether residual abnormalities after surgery may contribute to the high rates of anterior knee pain 2,31 and early-onset osteoarthritis seen in ACLR knees. 32,37 While conventional anterior-posterior laxity tests often fail to detect significant differences in ACLR knees, 8,40 numerous studies have found evidence of abnormal tibiofemoral kinematics during whole body movement such as gait, 10,49 downhill running, 55 and quasi-static lunges. 57 In particular, a number of publications report a shift toward external tibial rotation and medial translation in ACLR knees compared with healthy knees.…”
mentioning
confidence: 99%
“…Substantial interest has arisen in the ability of anterior cruciate ligament reconstruction (ACLR) to restore normal functional knee mechanics; as well, it is of interest whether residual abnormalities after surgery may contribute to the high rates of anterior knee pain 2,31 and early-onset osteoarthritis seen in ACLR knees. 32,37 While conventional anterior-posterior laxity tests often fail to detect significant differences in ACLR knees, 8,40 numerous studies have found evidence of abnormal tibiofemoral kinematics during whole body movement such as gait, 10,49 downhill running, 55 and quasi-static lunges. 57 In particular, a number of publications report a shift toward external tibial rotation and medial translation in ACLR knees compared with healthy knees.…”
mentioning
confidence: 99%
“…The fact that femoral tunnel dilation was not significant could be explained because of their location in the correct position, both by the posterior quadrant of Harner 29 and the posterior position of Aglietti methods. 30 Dilation of the tunnels has not been associated with greater instability in less than 5-year follow-up studies, 24,27,31 with no significant differences in the Lachman test or arthrometer measurements, but we have no longterm follow-up studies. The results of this study suggest that 15% of patients with grade IV tibial tunnel widening were associated with good outcomes in KT-1000 measurements.…”
Section: Discussionmentioning
confidence: 80%
“…While some authors detected widening in the first 3 or 4 months after surgery, 11 others defined it later: 10 to 12 months, 26 2 years, 9 or 5 years. 27 In contrast, others found no relationship between follow-up and tunnel dilation. 28 In our study, we observed a progression of the tibial tunnel dilation in the frontal plane in 43% of the patients between the mid-term and the final period, however 27% still dilating until final follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Despite variable techniques aiming to improve bone tunnel healing, bone morphogenetic protein (BMP) and calcium phosphate cement are still mainstays of treatment for optimization of the healing process in this purpose. Nebelung et al 66 evaluated midterm outcomes after transfemoral graft fixation using either a conventional or a modified technique and additional bone plug augmentation (BPA) of the femoral tunnel aperture after ACL reconstruction with a quadrupled hamstring autograft in 56 patients. Biomechanical pull-out testing showed that the ultimate failure load and stiffness of the reconstructed ACL in the experimental group were significantly higher than those in the control group at both 4 and 8 weeks (P < 0.05).…”
Section: Definitive Argument About Available Graft Choicesmentioning
confidence: 99%